1997
DOI: 10.1111/j.1475-6803.1997.tb00238.x
|View full text |Cite
|
Sign up to set email alerts
|

The Survival of Initial Public Offerings in the Aftermarket

Abstract: We estimate an accelerated failure time (AFT) model to investigate the effects of several characteristics suggested as indicators of firm survival for initial public offerings (lPOs). The results indicate that the survival time for IPOs increases with size, age of the firm at the offering, the initial return, IPO activity level in the market, and the percentage of insider ownership, while the survival time decreases with increases in the general market level at the time of the offering and the number of risk c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
234
7
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(270 citation statements)
references
References 20 publications
23
234
7
6
Order By: Relevance
“…The result of this study supports [8] and [17] who document negative relation between the level of underpricing and number of risk factors. The result is in contrast with [7]- [20] who found positive relation.…”
Section: Findings and Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The result of this study supports [8] and [17] who document negative relation between the level of underpricing and number of risk factors. The result is in contrast with [7]- [20] who found positive relation.…”
Section: Findings and Discussionsupporting
confidence: 75%
“…The higher the number of risks listed in the prospectus, the higher will be the level of underpricing [8]. Some studies document that the number of risks on prospectus is negatively related with initial return [8]- [17]. In contrast, others find a positive relationship between the numbers of risk and the level of underpricing [7]- [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, research suggests that firm size (Bhabra & Pettway, 2003;Hensler, Rutherford, & Springer, 1997), age (Hensler et al, 1997) and financial performance (Bhabra & Pettway, 2003;Platt, 1995) are negatively related to post-IPO firm failure. More recently research has shown that average management team tenure and IPO deal network embeddedness are also negatively related to post-IPO firm failure (Fischer & Pollock, 2004).…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…Further, their evidence shows a negative association between upward bias in management earnings forecasts and IPO performance in the first 12 months following the IPO. Hensler et al (1997) and Jain and Kini (2000) explain the usefulness of IPO prospectus data to potential investors. Their results indicate that prospectus information remains useful in the aftermarket over the short window of one year, although the value of this information declines rapidly with time.…”
Section: The Literature On Management Earnings Forecasts and Long-runmentioning
confidence: 99%